H8 scheduling control on nonlinear stochastic systems with partially unknown information - Liu, Y.; Yin, YanYan; Liu, F. (ICIC International, 2014)
In this paper, we propose a method for designing continuous gain-scheduled H1 controller for a class of stochastic nonlinear systems with unknown information. The stochastic nonlinear system under study is governed by a finite-state Markov process, but with partially known jump rate from one mode to another. Initially, gradient linearization procedure is applied to describe such nonlinear systems by several model-based linear systems. Next, H8 controllers are established for each linear model in terms of linear matrix inequalities. Finally, continuous gain-scheduled approach is employed to design continuous nonlinear controllers for the whole nonlinear jump system. A numerical example is given to illustrate the effectiveness of the developed techniques. © ICIC International 2014.